Learning During and From a Crisis: The Student-Led Development of a COVID-19 Curriculum. (15th September 2020) - Kochis, Michael; Goessling, Wolfram
Abstract : Problem: The speed and scope of the upheaval that COVID-19 inflicted on medical education made innovation a necessity. While medical students wanted high-quality, consolidated educational resources on COVID-19, the medical school faculty who typically produced such resources were increasingly burdened with clinical, administrative, and personal commitments. However, students eager to contribute to the pandemic response were well suited to create these instructional materials for their peers. Approach: In mid-March 2020, a group of students at Harvard Medical School came together to synthesize the key facts and collate the best existing educational materials about the COVID-19 pandemic into a unified learning resource. The materials were faculty reviewed and shared freely online. The curriculum now contains 8 modules that are updated regularly. Throughout this process, the student authors prioritized accessibility, iterative improvement, and effective pedagogy. Outcomes: To date, nearly 80, 000 users from 132 countries have accessed the curriculum. It has been referenced or incorporated into courses at Harvard Medical School and more than 30 other medical schools across the country. About 40% of all users are from outside the United States, and the materials have been translated into 28 languages. This effort has spurred a number of other educational initiatives led by medical student groups in the United States and abroad. Next Steps: As understanding of the COVID-19 pandemic is constantly changing, the student authors' immediate goal is to keep the curriculum up to date in the months to come. They plan to maintain existing partnerships with medical schools and student groups around the world while pursuing new opportunities to expand the curriculum's reach, provide education, and build community. Students and educators alike should leverage student-driven education efforts to benefit other learners both within and, importantly, beyond their institutions.